Development and validation of a quality of life scale for primary caregivers of children with cerebral palsy in Malaysia - Wei, Kelvin Ying @ Tang Shee (2025)
The quality of life (QoL) among primary caregivers of children with cerebral palsy (CP) is a critical concern, influencing both caregiver well-being and overall family dynamics. Understanding the factors that shape caregivers’ QoL is essential for developing effective support interventions. Yet, there are limited validated tools to assess caregiver QoL in the local context. This study aimed to develop and validate a culturally relevant QoL measure for primary caregivers of children with CP in Malaysia, conducted in three phases. Phase 1 involved a baseline quantitative study assessing primary caregiver QoL, Phase 2 focused on scale development, and Phase 3 validated the scale through exploratory factor analysis (EFA). Participants were recruited using key informant sampling in Phase 1 and purposive sampling in Phases 2 and 3, with a cross-sectional study design applied. In Phase 1, 159 primary caregivers (Mean age = 42.8 years, SD = 8.4) who attended health screening camps in Kelantan, Johor, and Sarawak participated. Their QoL was assessed using the Pediatric Quality of Life Inventory™ Family Impact Module (PEDSQL FIM) and analysed through descriptive analysis, single linear regression, and multiple linear regression. Results indicated that primary caregivers who attending health screening camps generally had good health-related QoL, family functioning, and overall QoL, with maternal education level and family income identified as key factors influencing all three. In Phase 2, a new Malay-language QoL scale was developed through literature review expert input, and in-depth interviews with eighteen local primary caregivers (Mean age = 39.3 years, SD = 7.28), identifying eight key themes: physical constraint, emotional distress, financial hardship, child’s difficult behavior, social support, acceptance, beliefs, and initiative for the child’s development. Items were generated and compiled into a draft scale, which underwent content validation by seven experts and pre-testing with 15 caregivers. In Phase 3, a hundred Malaysian primary caregivers (Mean age = 44.9 years, SD = 11.1) participated in the study. The newly developed scale, named the Primary Caregiver Quality of Life (PCQoL) scale, was tested for construct validity through EFA, concurrent validity through correlations with related constructs, and reliability via Cronbach’s alpha. The final 28-item version, covering eight domains, demonstrated strong validity and reliability in assessing QoL in the Malaysian primary caregiver context. This study provides valuable insights for healthcare providers to improve the QoL of primary caregivers of children with CP